2022
DOI: 10.3390/math10142423
|View full text |Cite
|
Sign up to set email alerts
|

Double Sources Queuing-Inventory System with Hybrid Replenishment Policy

Abstract: A hybrid replenishment policy in double sources queuing-inventory system is proposed. If the inventory level drops to the reorder point s, then a regular order of the fixed volume Q = S − s is generated to a slow and cheap source, where S denotes the maximum size of the system’s warehouse. If the inventory level falls below a certain threshold value r, where r < s, then the system instantly cancels the regular order and generates an emergency order to a fast and expensive source where the replenishment quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…A study has also observed that socially dominant cows are more likely to calve in an individual pen, while the presence of newly born calves to other cows may also influence calving behavior [13]. Therefore, some researchers proposed a queueing inventory system for calving management with a different approach in [14][15][16].…”
Section: Some Related Workmentioning
confidence: 99%
“…A study has also observed that socially dominant cows are more likely to calve in an individual pen, while the presence of newly born calves to other cows may also influence calving behavior [13]. Therefore, some researchers proposed a queueing inventory system for calving management with a different approach in [14][15][16].…”
Section: Some Related Workmentioning
confidence: 99%
“…QIS models with destructive customers hardly have been studied, although, as indicated above, they are accurate models of systems in real life. In papers [17][18][19][20], the authors assumed that the arrival of destructive customers causes the level of the inventory is reduced only by one. However, there are many realistic QISs in which upon arrival of destructive customers all items damage together.…”
Section: Introductionmentioning
confidence: 99%